Pharmacological activation of GPX4 ameliorates doxorubicin-induced cardiomyopathy - Chuying Huang; Yishan Guo; Tuo Li; Guogen Sun; Jinru Yang; Yuqi Wang; Ying Xiang; Li Wang; Min Jin; Jiao Li; Yong Zhou; Bing Han; et al. (Redox Biology, 2024)
Due to the cardiotoxicity of doxorubicin (DOX), its clinical application is limited. Lipid peroxidation caused by excessive ferrous iron is believed to be a key molecular mechanism of DOX-induced cardiomyopathy (DIC). Dexrazoxane (DXZ), an iron chelator, is the only drug approved by the FDA for reducing DIC, but it has many side effects and cannot be used as a preventive drug in clinical practice. Single-nucleus RNA sequencing (snRNA-seq) analysis identified myocardial and epithelial cells that are susceptible to DOX-induced ferroptosis. The glutathione peroxidase 4 (GPX4) activator selenomethione (SeMet) significantly reduced polyunsaturated fatty acids (PUFAs) and oxidized lipid levels in vitro. Consistently, SeMet significantly decreased DOX-induced lipid peroxidation in H9C2 cells and mortality in C57BL/6 mice compared to DXZ, ferrostatin-1, and normal saline. SeMet can effectively reduce serum markers of cardiac injury in C57BL/6 mice and breast cancer patients. Depletion of the GPX4 gene in C57BL/6 mice resulted in an increase in polyunsaturated fatty acid (PUFA) levels and eliminated the protective effect of SeMet against DIC. Notably, SeMet exerted antitumor effects on breast cancer models with DOX while providing cardiac protection for the same animal without detectable toxicities. These findings suggest that pharmacological activation of GPX4 is a valuable and promising strategy for preventing the cardiotoxicity of doxorubicin.